Protecting Human Research Subjects as Human Research Workers - Holly Fernandez Lynch (Human Subjects Research Regulation, 2014)
The changes proposed to the Common Rule in the ANPRM were primarily intended to enhance protections for human subjects while reducing burden on researchers. However, due to a continued view of human subjects research as an exceptional endeavor that ought to be governed by exceptional rules (Sachs 2010 ; Miller and Wertheimer 2010; Wilson and Hunter 2010), the government and interested stakeholders have failed to take this once-in-two-decade opportunity to consider some enhanced protections that could be appropriately imported from a potentially unexpected but analogous setting—the workplace. In this chapter I flesh out the analogy between human subjects in